Opportunities and limitations for the introduction of circular economy principles in EU aquaculture based on the regulatory framework. (24th August 2021) - Regueiro, Leticia; Newton, Richard; Soula, Mohamed; Méndez, Diego; Kok, Björn; Little, David C.; Pastres, Roberto; Johansen, Johan; Ferreira, Martiña
Abstract: EU aquaculture produces only a small fraction of the internal demand of aquatic foods, but boosting this activity must be done in compliance with high standards of environmental protection and social benefits, as fostered by the policies on circular economy recently launched by the EU. Nevertheless, the assessment of the environmental sustainability of aquaculture and other food production systems is complex, due to the different tools and approaches available. Moreover, the current EU regulatory framework may be restricting the options to implement some circular solutions. This paper examines the controversies related to the assessment of environmental impacts of aquaculture processes and the different available circular solutions, with a focus on the best options to valorize aquaculture side streams and how current regulatory burdens and gaps should be solved.